PENGARUH PERTUMBUHAN EKONOMI KREDIT NON LANCAR DAN TINGKAT SUKU BUNGA TERHADAP PENYALURAN KREDIT BANK UMUM KALIMANTAN BARAT - B01109070, MELY (Jurnal Pembangunan dan Pemerataan, 2014)
Credit distribution is the distribution of funds from the banks against any individual or institution to improve production . Lending done by banks is influenced by external and internal factors . External factors such as the economic condition of the debtor and the views of economic growth , while the internal factor can be measured by deposits, CAR, NPL, ROA, and LDR. This study aimed to examine the effect of simultaneously and partially between economic growth , the non-current loans and interest rates on commercial bank lending in West Kalimantan . Overall object of this study using a commercial bank from year 2003 to 2012 . Data analysis technique used is multiple linear regression , t test for testing while the partial f test for simultaneous testing . Based on the partial test results , economic growth and a significant negative effect terhdap lending , non -current loans ( NPL ) and no significant negative effect on lending , while lending rates and signigfikan negative effect on lending. Based on simultaneous testing proves that economic growth , non -current loans ( NPLs ) and loan interest rates simultaneously affect the lending of commercial banks in West Kalimantan . Keywords : Economic Growth , Non -Current Loans , Interest Rate and Credit Distribution